Needs Analysis for Developing a Brain-Based Metacognitive Learning Model to Enhance Critical Reading in Primary Schools - Prasetyo, Teguh; Yufiarti, Yufiarti; Supena, Asep (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study aims to analyze the pedagogical and contextual needs underlying the development of a learning model designed to improve students' critical reading skills in primary schools. The urgency of this research arises from various global and national assessments that indicate a declining trend in students' reading literacy performance. Data from the 2022 PISA report show that Indonesian students' reading abilities remain below the OECD average, while findings from PIRLS 2021 highlight the importance of inferential and evaluative comprehension as essential benchmarks for global reading literacy. This study employed a mixed-method approach involving 30 students and several grade 5 teachers from primary schools in the Bogor district. Data were collected through open-ended and closed-ended questionnaires for students, as well as teacher interviews, to examine current practices in reading instruction within Indonesian language learning. The findings reveal that students' critical reading skills remain underdeveloped, particularly at the literal, inferential, and evaluative levels. Most students rely heavily on teacher assistance, lack metacognitive strategies, and demonstrate limited ability to reflect on and regulate their reading comprehension. These findings underscore the urgent need to design a learning model that integrates Brain-Based Learning (BBL) principles with metacognitive assessment strategies. Such integration is expected to foster emotionally engaging and cognitively supportive learning environments that empower primary school students to become more critical and self-regulated readers.